حل المجلس الشعبي الوطني - غدير أحمد, أحمد بدر الدين (جامعة الوادي -University eloued, 2022)
بعد الاستقلال عملت الجزائر جاهدة على بناء دولة ديمقراطية تجسد طموحات أفرادها، من خلال ضمان الحقوق والحريات ولتحقيق هذا المسعى بدأت في العمل على قيام نظام سياسي ينعش الحياة السياسية والقانونية، ويساهم في بناء مؤسسات الدولة والحفاظ على استقرارها واستقلاليتها، وفي هذا الشأن أسس المجلس الشعبي الوطني، الذي يعتبر أول هيئة يناط لها دور البرلمان والذي يعد بمثابة ميلاد السلطة التشريعية في الجزائر، ومن مهامه ممارسة التشريع ورقابة عمل الحكومة، مما سبب مشاكل قد تنعكس بالسلب على الأمة، وهو ما جعل المشرع الجزائري في تلك الفترة يخول آلية اللجوء إلى حل المجلس الشعبي الوطني، وهذا كان واضحا في الدستور 1963 وفي سبيل تحقيق التوازن بين السلطتين التنفيذية والتشريعية جاء في مضمون نص المادة 56 من الدستور يحل البرلمان تلقائيا في حالة سحب الثقة من أعضاء الحكومة من تقديم رئيس الجمهورية لاستقلالية، وبالتالي حل المجلس الشعبي الوطني هو حق مكرس دستوريا منذ دستور 1963، ولا يزال مكرس إلى غاية الدستور الحالي . وعليه في هذا الفصل أبرز بشكل أكثر الإطار المفاهيمي لآلية حل المجلس الشعبي الوطني (المبحث الأول ) والجانب الإجرائي لآلية حل المجلس الشعبي (المبحث الثاني). المبحث الأول: الاطار المفاهيمي لآلية حل المجلس الشعبي الوطني تعتبر أداة حل المجلس الشعبي الوطني من بين أخطر الوسائل التي تدعم مكانة السلطة التنفيذية أمام البرلمان وهو بمثابة امتياز لها، تمتلك السلطة التشريعية وسائل عديدة وكثيرة يمكن لها من خلالها مراقبة السلطة التنفيذية، لعلها أهمها هب آثارة المسؤولية للحكومة من طرف نواب المجلس الشعبي الوطني عن طريق تقديم سبعة نواب لملتمسي الرقابة، وذلك من خلال رئيس الدولة ويرجع السبب من وراء إعطاء المؤسس الدستوري لرئيس الجمهورية الحق في حل المجلس الشعبي الوطني إلى رغبته في تحقيق التوازن بين السلطات في مجال الرقابة.We devoted the chapter of our research to studying the conceptual framework of the mechanism of dissolving the National People's Assembly, as we highlighted the various definitions to give them to the mechanism of the solution. A king, a prince, or a president of a republic. But if the solution takes place at the request of the ministry in the event of a dispute between it and Parliament, we will be before the image of the ministerial solution, and the solution may be by force of law in certain cases specified by the constitution. What is termed as self-dissolution, and as the popular will can be the source of the solution, it is issued by direct popular will, which is known as the popular solution. Chapter Summary In this chapter, we dealt with in the first topic the constitutional procedures that precede the dissolution of the People’s National Assembly, which is a set of procedures carried out by the President of the Republic. Consultation before dissolving the People’s National Assembly, and this is what we discussed in the first section, then holding prior legislative elections, which we discussed in the second section, then finally the self-dissolution of the National People’s Assembly, and this is what we discussed in the third section. Constitutionally empowered to dissolve the People’s National Assembly, so we divided it into two branches: In the first section, we dealt with the authority authorized to issue a decree dissolving the People’s National Assembly, which is the President of the Republic, as he is the protector of the constitution, based on Article 147 of the 2016 Constitution. Signing In the second topic, we discussed the legal consequences resulting from the mechanism of dissolving the National People's Assembly, as it is from the stage of completing the procedure. A, which is represented in the set of results that fall on the legislative and executive bodies. As for those related to the legislative institution, it is represented in the disruption and inertia of the function of the National Assembly, as well as the application of the theory represented in the loss of members of the National People’s Assembly and their parliamentary
ماستر اداري
Keywords: المجلس الشعبي الوطني، السياسة ،البرلمان، السلطة التنفيذية; National People's Assembly, politics, parliament, executive authority.